PRELIMINARY INVESTIGATION OF THE EFFECT OF DIFFERENT DOSES GNRH (GONADDOTROPIN RELEASING HORMON ) AND BOVINE LH (LISTERING HORMON) ON PLASMA LH AND TESTOSTERON CONCENTRATION IN MALE DOGS - Junaidi, Aris; Trigg, T.E. (2002)
Six male adult dogs were randomized into 2 equal groups. Groups 1, dogs were